O PASSADO À VISTA. ELEMENTOS DE APRENDIZAGEM E CULTURA HISTÓRICA NO LIVRO “1808” - Gelbcke, Juliana (2016)
Facing the great impact of the story books talking about history and thinking the journalist as a professional who does not have the same interests and theoretical and methodological concerns of academia, this research, from worries about the didactics of history (BERGMANN, 1990; RÜSEN, 2001), investigates what the journalists produce when writing about history, what kind of knowledge their productions spread in public space and how the reader relates to this knowledge. For that reason, this study analyses one of the largest sales phenomena of recent years, the book 1808 - Like a mad queen, a fearful king and a corrupt court deceived Napoleon and changed the History of Portugal and Brazil by the writer and journalist Laurentino Gomes. The book is designed as a product of the public history, which, somehow, is part of a more comprehensive historical culture. Aiming to investigate how Laurentino Gomes builds his narrative and what one can learn from it, 1808 is analysed from the three dimensions of historical culture: cognitive, aesthetic and political (Rüsen, 1994).From then, this analysis is compared with the analysis of the reader's opinion, through a questionnaire over the internet. This questionnaire was also thought from the three dimensions of historical culture and its issues were analysed based on content analysis methodology (BARDIN, 2011). It was sought to investigate, for example, the main reasons that lead the reader to be drawn by the 1808 (aesthetic dimension) if and why he trusts, or not, in this content in the book (cognitive dimension) and if he was able to take some lesson, learn something that will help him to understand / interpret better his present from the historical data available in 1808 (political dimension). As shown above, the book provides a knowledge that does not escape from the common sense of readers and dialogues with the knowledge that readers had access at school and also the one that is spread by the mainstream media. The book 1808 does not, nor intends to bring a new discussion in relation to historiographical debates, and without the same academic rigor of historians, Laurentino Gomes contributes to popularize the story in a very efficient and seductive way, paying special attention to aesthetic elements, which consist, among other things, in colloquial language, a story in the saga format with dabs of romance and fiction, the humanization and exploration of the psychological profile of the great historical characters and a touch of humour to portray some passages. Contributing therefore for the readers to approach the past, becoming eyewitnesses of history, increasing empathy at times for the past and facilitating the understanding of the historical content. On the other hand, when it overvalues the aesthetic elements, 1808 ends up committing some slips to academic eye, compromising, at times, the cognitive dimension of the work, leading, for example, some readers to make certain judgments and anachronisms.